The Tuvan language on the Internet: Representation, problems and prospects - Ondar, Choigan G.; Dongak, Venera S.; Mongush, Dolaana Sh. (The New Research of Tuva, 2023)
The development of information and communication technologies has led to the extension of the sphere where the Tuvan language functions on the Internet. This article presents an overview of web resources in Tuvan, their problems and prospects.While considering the representations of the Tuvan language, the authors classified Internet resources into four types: information sites, social networks and messengers, web services and online tools, mobile apps. For instance, it has been found out that only the website of the newspaper “Shyn” and the portal “Tyvanyn chogaalchylary — Writers of Tuva” offer an interface and full content in Tuvan. The official websites of Tuvan institutions do not have a Tuvan version of the interface and contain little information in the Tuvan language: the largest number of news items in Tuvan is presented on the website of the Government of the Republic of Tuva (45% of the total number of news), and the website of the Ministry of Economic development and Industry of the Republic of Tuva contains the least number of news items in Tuvan among the analyzed web resources (only 0.16%).Despite the fact that Tuvan is one of the official languages of the Republic of Tuva, the scope of its functioning is limited. The difference between the demand for the Tuvan language on official websites and in social networks is evident. It can be observed that the authorities themselves do not actively use and develop the Tuvan language on the Internet, although they champion the development of the language. And without special state support the society seeks to expand the functioning of the Tuvan language on the Internet.Tuvan is the language of communication in the VK social network and the Viber messenger. There are language tools for users who know Tuvan, including Wikipedia in Tuvan, online dictionaries, Tuvan keyboard layout, electronic corpus, a data collection platform for developing Tuvan online translation tools, and a morphological analyzer. There are also several apps available in the App Store and Google Play.
Keywords: Tuvan; digitalization of the Tuvan language; digital stability of the language; Internet; web space